2017
DOI: 10.1039/c7nj00619e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ferrocenylmethylidene and arylidene substituted camphane based compounds as potential anticancer agents

Abstract: A series of new compounds with a camphane moiety was synthesized, and some of the ferrocene-containing compounds showed promising anticancer activity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Other aldehydes (2-6 and 16-18) were used as commercial products. The formation and characterization of some desired ketones (22-23, 26-27) was described elsewhere, in different studies, not related to the present investigation: Grošelj et al [49] (for 22), Nevalainen et al [50] (for 23), Salisova et al [51] (for 26), Kamenova-Nacheva et al [16] (for 27).…”
Section: Chemistrymentioning
confidence: 71%
See 1 more Smart Citation
“…Other aldehydes (2-6 and 16-18) were used as commercial products. The formation and characterization of some desired ketones (22-23, 26-27) was described elsewhere, in different studies, not related to the present investigation: Grošelj et al [49] (for 22), Nevalainen et al [50] (for 23), Salisova et al [51] (for 26), Kamenova-Nacheva et al [16] (for 27).…”
Section: Chemistrymentioning
confidence: 71%
“…Bearing in mind our previous studies, it is noteworthy that arylidene camphanes exhibit enhanced cytotoxicity, depending on the nature of the arylidene moiety. [16] Thus, only compounds 40 and 55 from this study can be considered as safe for further application as antimicrobial agents (Table 3), since they preserve its low cytotoxicity even at long time treatment (72 h). Other active compounds in Table 3 (30, 41, 42, 44, 45 and 48) need further elucidation of their cytotoxicity and therapeutic windows.…”
Section: Cytotoxicity and Cell Viability Studiesmentioning
confidence: 98%
“…We found that the p53 positive cancer line A549 showed a lower IC50 value, probably due to the fact that H1299 cells have a homozygous partial deletion of the p53 protein, and lack expression of p53 protein. In our previous studies, it was demonstrated that H1299 cells are less sensitive to the treatment with classical chemotherapeutic drugs such as cis-platin and Tamoxifen [22,27] as well; thus, the lack of expression of p53 is probably responsible for the observed higher drug resisters. It was interesting to examine the extent to which this cellular toxicity (mortality) is caused by the process of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic activity of CBD was tested on a panel of two human lung cancer cell lines using the MTT assay as described previously [22]. Briefly, 2000 cells were seeded into each well in 100 µL in octuplicates in 96-well flat-bottom plates and incubated for 24 h (37 °C, 5% CO 2 ) to allow attachment of the cells.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…In a study by Naik et al in 2017, a radioligand was developed with 1-adamantyl amine for PET imaging [7]. In another study done in 2017, ferrocenylmethylidene and arylidene substituted adamantane ring based compounds as potential anticancer properties were synthesized [8]. In another study, biologically active adamantyl hybrid compounds were synthesized [9].…”
Section: Introductionmentioning
confidence: 99%